A short computerized cognitive training may affect cortical sources of rsEEG rhythms in Alzheimer's disease patients. (20th December 2022) - Lizio, Roberta; Percio, Claudio Del; Noce, Giuseppe; Lopez, Susanna; Janson, Jessica; Barulli, Maria Rosaria; Logroscino, Giancarlo; Musaro, Cinzia; Scianatico, Gaetano; Rossini, Paolo Maria; Lacidogna, Giardano; Gesualdo, Loreto; et al.
Abstract: Background: Previous evidence showed abnormal posterior sources of resting‐state electroencephalographic (rsEEG) delta (<4 Hz) and alpha (about 8‐12 Hz) rhythms in patients with Alzheimer's disease (AD) as cortical neural synchronization markers in quiet wakefulness. We tested whether daily computerized cognitive training (CCT), for a short period, with an application of serious games, may affect these mechanisms, Method: Clinical and rsEEG data were collected in AD and Parkinson's disease (PD) patients with cognitive deficits and normal elderly (Nold) subjects. The rsEEG data in the patients were recorded before and after the two weeks of computerized cognitive training. Cortical rsEEG sources were estimated by exact low‐resolution brain electromagnetic tomography (eLORETA). Result: AD and PD patients were both characterized by increased performance scores in the execution of the neuropsychological tasks after the CCT program. In AD patients, no statistical difference (p >0.05) was observed in the rsEEG markers after the CCT program. In PD patients, the widespread delta source activities significantly decreased after cognitive training. Conclusion: These preliminary results suggest that the CCT program with this application of serious games differently affects the cortical neural synchronization mechanisms of rsEEG of the AD and PD patients. In the AD patients, it may have no effect, possibly because of the severely compromised integrity of the cholinergic system in those patients.